Answer :

Given that, cos 2θ cos 2ϕ + sin2(θ–ϕ) – sin2(θ + ϕ)

= cos 2θ cos 2ϕ + sin(θ–ϕ+ θ + ϕ)sin(θ–ϕ- θ – ϕ)

[sin2A – sin2B = sin (A + B) sin (A – B)]

= cos 2θ cos 2ϕ + sin 2θ. sin(- 2ϕ)

= cos 2θ cos 2ϕ - sin 2θ. Sin 2ϕ [ sin(-θ) = -sin θ]

= cos 2(θ + ϕ) [ cos x cos y – sin x sin y = cos(x + y)]

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses

True and False<brMathematics - Exemplar

Find the values oRD Sharma - Mathematics

Prove that :
RD Sharma - Mathematics

The value of cos<Mathematics - Exemplar

The value of sin Mathematics - Exemplar

cos 2θ cos 2<spanMathematics - Exemplar

The value of <spaMathematics - Exemplar

If <span lang="ENMathematics - Exemplar

If <span lang="ENMathematics - Exemplar

Fill in the blankMathematics - Exemplar